Bach Perspectives, Volume 6 : J. S. Bach's Concerted Ensemble Music, The Ouverture - Butler, Gregory (Book collections on Project MUSE., 2007)
As the official publication of the American Bach Society, Bach Perspectives has pioneered new areas of research in the life, times, and music of Bach since its first appearance in 1995. In a series long known for its major essays by leading Bach scholars and performers, Bach Perspectives, Volume 6 is no exception. This volume opens with Joshua Rifkin's seminal study of the early source history of the B-minor orchestral suite. It not only elaborates on Rifkin's discovery that the work in its present form for solo flute goes back to an earlier version in A minor, ostensibly for solo violin, but also takes this discovery as the point of departure for a wide-ranging discussion of the origins and extent of Bach's output in the area of concerted ensemble music. Jeanne Swack presents an enlightening comparison of Georg Phillip Telemann's and Bach's approach to the French overture as concerted movements in their church cantatas, and Steven Zohn views the B-minor orchestral suite from the standpoint of the "concert en ouverture," responding to Rifkin by suggesting that the early version of the B-minor orchestral suite may also have been scored for flute [Publisher description].